Effect of chitosan combined with hyaluronate on promoting the recovery of postoperative facial nerve regeneration and function in rabbits - Liu, Huawei (Exp Ther Med, 2018)
To determine better solutions for postoperative nerve functional recovery, the effects of chitosan and hyaluronate on perineural scar formation and neural function recovery were investigated in 40 rabbits. Rabbits were randomized into 4 groups: A (chitosan), B (chitosan + hyaluronate), C (hyaluronate) and D (control). The rabbits underwent the same parotidectomy surgery, but different materials were used to cover the operated nerves. By evaluating specific indicators, including vibrissae motion tests, neural electrophysiological examinations and extraneural examinations, it was revealed that the amplitude of vibrissae motion of all groups had increased 6 weeks after surgery. The recovery of Group B was superior compared with all other groups at 4 and 12 weeks post-surgery; however no significant differences were detected. Group B exhibited a great number of nerve fibers, thicker myelin sheath and greater nerve conduction velocity. In summary, the use of a chitosan conduit combined with sodium hyaluronate gel may prevent perineural scar formation in facial nerves and promote nerve functional recovery.